Influence of social media on parents' attitudes towards vaccine administration - Khalid A Al-Regaiey; Wjdan S Alshamry; Reem A Alqarni; Majd K Albarrak; Rinad M Alghoraiby; Danah Y Alkadi; Leen R Alhakeem; Shahid Bashir; Muhammad Iqbal (Taylor & Francis Group, 2022)
Vaccination has had tremendous impact on human health. The tendency to hesitate or delay vaccination has been increasing, which has contributed to outbreaks of vaccine-preventable diseases. This cross-sectional study aimed to investigate the prevalence of childhood vaccine hesitancy and social media misconceptions in vaccine refusal among randomly selected parents from October 2019 through March 2020 in the outpatient clinics of King Khalid University Hospital, Riyadh, Saudi Arabia. The data were collected using a three-part questionnaire: the socio-demographic and economic questions, the Parents' Attitudes about Childhood Vaccines (PACV) survey, and questions concerning social media use. Based on the PACV survey tool, 37 parents (11%) scored a value > 50 and were suggested as hesitant (8% hesitant and 3% very hesitant). Overall, 288 parents (89%) scored < 50, hence deemed to not be hesitant about childhood vaccination. There was no significant association between high educational level or social media exposure with vaccine hesitancy. The most commonly used social media platform was Twitter (40%). In conclusion, we report a low prevalence of vaccine hesitancy about childhood vaccination among parents, with no significant impact of education level or social media on vaccine hesitancy. Further studies are required to replicate these findings in other regions and cities to generalize these observations for Saudi Arabia.